Permanence and resistance of the remaining communities of quilombos no Paraná - Campos, Margarida de Cássia; Gallinari, Tainara Sussai (Geosaberes; Vol 8 No 15 (2017): May - Aug, 2017)
In Paraná, a slavery occurred in the areas of older occupation, a slave labor was used in the cultivation of mate grass or in the practice of livestock. Where hidden slaveholdings are, quilombos have emerged and today are territories called Remaining Communities of Quilombos (CRQs). This article tries to understand the permanence and resistance of CRQs in Paraná through a bibliographical survey about the slavery process in the state, a quilombo view of a territory, the context in which CRQs emerged and their current spatiality and the strategies of resistance of the Communities With this, it was observed that a conquest of quilombola lands is a continuous process of struggle, and has as obstacles as uninterrupted threats of losses of their lands, especially due to the expansion of crops for export and areas of plantation of commercial use.
Keywords: Comunidades Remanescentes de Quilombos; Paraná; Território